2021
DOI: 10.1093/ejcts/ezab296
|View full text |Cite
|
Sign up to set email alerts
|

The questionable benefit of pectus excavatum repair on cardiopulmonary function: a prospective study

Abstract: OBJECTIVES Since the introduction of the minimally invasive technique for repair of pectus excavatum (MIRPE), increasing numbers of patients are presenting for surgery. However, controversy remains regarding cardiopulmonary outcomes of surgical repair. Therefore, the aim of our prospective study was to investigate cardiopulmonary function, at rest and during exercise before surgery, first after MIRPE and then after pectus bar removal. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Seven of the 11 studies showed overall improvement in CPET variables after surgery with mean increased of VO 2max ranging from 6% to 40% and mean improvements in in oxygen pulse of 10%–44% 10 12–14 18 27 28. Four studies found CPET variables to be unchanged after surgery 15 17 20 25. Six of the studies demonstrated improvements in VO 2max and eight showed improvements in O 2 pulse.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Seven of the 11 studies showed overall improvement in CPET variables after surgery with mean increased of VO 2max ranging from 6% to 40% and mean improvements in in oxygen pulse of 10%–44% 10 12–14 18 27 28. Four studies found CPET variables to be unchanged after surgery 15 17 20 25. Six of the studies demonstrated improvements in VO 2max and eight showed improvements in O 2 pulse.…”
Section: Resultsmentioning
confidence: 95%
“…Sixteen studies have investigated exercise testing after surgical repair of PEx 14–27. The primary outcome measures reported were maximal oxygen consumption (VO 2max ), VO 2max per kilogram and oxygen pulse, which is a surrogate for stroke volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, sternum is depressed to the vertebral column at the xiphoid process level. Patients with pectus excavatum deformity are most often asymptomatic, but may encounter respiratory problems when depression is significant, and this circumstance reduces the capacity of the chest cavity and causes pressure on the heart (4). Different surgical techniques are described in the treatment of pectus excavatum.…”
Section: Introductionmentioning
confidence: 99%
“…The questionable benefit of Pectus Excavatum repair on cardiopulmonary function: a prospective study. (Del Frari et al, 2021) 19 pacientes con Pectus Excavatum…”
mentioning
confidence: 99%